PWE-028 A Novel Assay for The Direct Detection of Deoxythioguanosine (DTG) in DNA from Patients On Azathioprine Using Liquid Chromatography and Tandem Mass Spectrometry (LC-MS/MS). (17th August 2016) - Coulthard, S; Berry, P; McGarrity, S; Redfern, C
Abstract : Introduction: The correlation between thiopurine drug metabolite levels in red blood cells (RBC) and clinical response is currently under debate, with some studies reporting a good correlation whereas others report a poor correlation. However, without a suitable alternative assay this is the only method presently available to guide dosing of patients treated with thiopurine drugs: azathioprine (AZA), mercaptopurine (MP) or thioguanine. Biologically, this method is not perfect given that RBC lack the critical drug-metabolising enzyme inosine-monophosphate dehydrogenase, which is central to the bioconversion of MP to thioguanine nucleotides that are then incorporated as fraudulent bases into nucleic acids. To try to get a better indicator of drug response and hence clinical outcome, we have developed a sensitive liquid chromatography- tandem mass spectrometry (LC-MS/MS) assay to measure incorporated dTG in the DNA isolated from peripheral blood mononuclear cells of patients treated with thiopurines Methods: DNA was isolated from blood samples collected from IBD patients on thiopurines. DNA was denatured then digested using P1 nuclease followed by treatment with alkaline phosphatase and finally diluted in MilliQ water prior to analysis. A total of 0.2 μg of DNA in 50 µL was injected for chromatographic separation followed by analysis on an API4000 triple quadrupole mass spectrometer. Standard curves and controls were validated and samples analysed to determine number of moles of dTG/105 5 moles of dA. Results: From a small cohort of 20 AZA treated IBD patients (10 Crohn's Disease and 10 Ulcerative Colitis) with dTG levels of 0.18 to 11.3 moles dTG/105 5 moles dA (approximately 5 to 340 femtomoles/μg DNA) were detected with no detectable dTGs in un-treated patients. The intra- and inter-assay variability was below 7.8% and 17.0% respectively with a detection limit of 15.5 pg (54.7 femtomoles) and was quantified in DNA samples relative to endogenous dA. Conclusion: This method enables the direct detection of a cytotoxic thiopurine metabolite in an easily obtainable, stable sample and will facilitate a better understanding of the mechanisms of action of these inexpensive yet effective drugs. Disclosure of Interest: None Declared